Lineage diversification, homo- and heterologous reassortment and recombination shape the evolution of chicken orthoreoviruses - Farkas, Szilvia L.; Marton, Szilvia; Dandár, Eszter; Kugler, Renáta; Gál, Bence; Jakab, Ferenc; Bálint, Ádám; Kecskeméti, Sándor; Bányai, Krisztián (Scientific reports, 2016)
The near complete genome sequences of ten field avian orthoreovirus (ARV) strains collected from young chicken between 2002 and 2011 in Hungary have been determined in order to explore the genetic diversity and evolutionary mechanisms affecting ARVs in this region. Sequence analyses and phylogenetic calculations revealed similar geographic distribution and distinct evolution in case of eight studied strains that were closely related to the recently described Hungarian strain T1781. The remaining two strains showed the highest similarity with the US origin AVS-B. The topology of the phylogenetic trees of certain segments was affected by several potential homologous reassortment events between strains of Hungarian, Chinese and US origin. Analyzing the μB gene a possible heterologous reassortment event was identified in three Hungarian strains. Recombination events were detected in as much as a dozen cases implying that beside point mutations and reassorment this mechanism also plays an important role in the diversification of ARVs. All these mechanisms in concert may explain the reduced effectiveness of immunization using commercial vaccine strains.